The Role of Men During Pregnancy: A Cross-Sectional Study of Perceptions and Beliefs of Primary Caregivers in Tanzania. (January 2022) - Niedfeldt, Heidi J.; Sever, Trent E.; Smith, Rilee; Davis, Elizabeth A.; Mulokozi, Generose; Torres, Scott; Linehan, Mary; Dobies, Kerry Ann; Hoj, Taylor; West, Joshua H.; Hall, P. Cougar; Crookston, Benjamin T.
This study examined the relationship between men's involvement and primary caregivers' antenatal visits, acquiring antenatal tablets, and working less during pregnancy. A cross-sectional survey was conducted with 5, 000 Tanzanian primary caregivers living in households with one or more children under the age of 2 years. Results indicated that primary caregivers who received help from their husband/partner, or perceived that men in their community helped their pregnant spouses, were more likely to practice healthy antenatal care behaviors, including attending antenatal visits, acquiring antenatal tablets, and working less during pregnancy. Similarly, women who thought that all their friends receive help from their husbands/partners were twice as likely to reduce their workload during their pregnancy. These findings suggest the importance of male involvement and support during pregnancy in order to improve antenatal care, reduce workload, and increase tablet consumption among primary caregivers.